2016
DOI: 10.1016/j.immuni.2016.04.015
|View full text |Cite|
|
Sign up to set email alerts
|

PSGL-1 Is an Immune Checkpoint Regulator that Promotes T Cell Exhaustion

Abstract: Summary Chronic viruses and cancers thwart immune responses in humans by inducing T cell dysfunction. Using a murine chronic virus that models human infections, we investigated the function of the adhesion molecule, P-selectin glycoprotein ligand-1 (PSGL-1) that is upregulated on responding T cells. PSGL-1-deficient mice cleared the virus due to increased intrinsic survival of multifunctional effector T cells that had downregulated PD-1 as well as other inhibitory receptors. Notably, this response resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
144
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(155 citation statements)
references
References 51 publications
(59 reference statements)
6
144
1
4
Order By: Relevance
“…Mechanistically, we found that engaging PSGL-1 with anti-PSGL-1 antibody (clone 4RA10) paired with TCR stimulation resulted in ERK and AKT early dephosphorylation, indicating that PSGL-1 signaling can extinguish TCR signaling events [67]. These findings are consistent with inhibitory receptors like PD-1 mediating T cell exhaustion through dampening TCR signals [98, 99], however how PSGL-1 signaling contributes to this is unknown (Figure 4C).…”
Section: Functions Of Psgl-1 In T Cellsmentioning
confidence: 63%
See 4 more Smart Citations
“…Mechanistically, we found that engaging PSGL-1 with anti-PSGL-1 antibody (clone 4RA10) paired with TCR stimulation resulted in ERK and AKT early dephosphorylation, indicating that PSGL-1 signaling can extinguish TCR signaling events [67]. These findings are consistent with inhibitory receptors like PD-1 mediating T cell exhaustion through dampening TCR signals [98, 99], however how PSGL-1 signaling contributes to this is unknown (Figure 4C).…”
Section: Functions Of Psgl-1 In T Cellsmentioning
confidence: 63%
“…Interestingly, one report showed that Selplg −/− mice had increased numbers of T cell effectors producing IFN-γ, IL-4, and IL-17 in skin, corresponding to Th1, Th2, and Th17 populations, but no differences in Tregs [86]. This spontaneous autoimmune phenotype was not reported in other studies [23, 67, 70] indicating that potential microbiota and/or strain differences may modulate effector responses in Selplg −/− animals.…”
Section: Functions Of Psgl-1 In T Cellsmentioning
confidence: 93%
See 3 more Smart Citations